Dinamika Perkembangan Jurusan Sejarah Sebagai Lembaga Akademik Tahun: 1954-2018 dari PTPG ke UNP - Yola Maiza Chandra; Mestika Zed; Aisiah Aisiah (Jurnal Kronologi, 2019)
This article talks about the history department as the oldest department at Padang State University. This research tries to explain the development of the history department starting from the formation of the history department since the PTPG Batusangkar period to the UNP. The purpose of this study is to describe the development of the Department of History as the oldest department. This research was conducted using the method of historical writing consisting of four stages of source collection (heuristics), sources of criticism (verification), concluding reliable testimony (interpretation), and final writing (historiography). The results of this study indicate that the Department of History is one of the departments sheltered by the Faculty of Social Sciences since 1999 at Padang State University until now. The history department is one of the oldest departments that was also formed with five other departments during the PTPG Batusangkar. These higher education institutions experienced changes that could be classified in four periods, namely: 1) the initial period of the PTPG Batusangkar in 1954-1956; 2) Transition period, namely FKIP Unand Bukittinggi in Batusangkar 1956-1958, FKIP Andalas University Padang in 1958-1964, IKIP Jakarta-Padang Branch, 1964-1965; 3) IKIP Padang period as Stand Alone Institution in 1965-1999; 4) the period of Padang State University (UNP) in 1999-present. As one of the oldest majors at UNP, the history department has undergone many changes from time to time. Both in terms of physical and non-physical. Physical changes can be seen and felt useful by the Department of History such as lectures, offices, departments and other lectures. While for non-physical facilities, the history department has teaching staff and administrative staff who can support the smooth running of the history department. Since last year, the Department of History has accredited A from the National Accreditation Agency for Higher Education (BAN-PT), precisely in 2017